Incidence of Entamoeba Gingivalis and Trichomonas Tenax in the Oral Cavity of Periodontal and Patients Under Chemotherapy, Confirmed with in Vivo Study - Dhilal Mahdi Al-Muathen1, Luma Amer Yasir2, Hayat Ghaith Sachit3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Aim: The study aimed to evaluate the impact of occurrences Entamoeba gingivalis, and Trichomonas tenax with periodontal in one hand and patients receiving chemotherapy on the other hand and compared to normal subjects. And evaluate the pathogenecity of these parasites In Vivo. Materials and Method: A total of 80 patients, 30 with Periodontitis attending AL-Karama dentistry center, and 20 patients under chemotherapy referred to the national center of hematology- Mustanasiriyah University, Iraq, were involved in this study. And the last 30 subjects were considered as control with good oral condition. Scrapings of gums were taken and examined immediately microscopically,once by wet mount smear, and the other stained with Giemsa-Romanovesky. The positive samples were cultured on special cultures for the experimental part and then spread on the gingival margins of three groups of rats (for each parasite), the first was given immunosuppressive drug, while the other two groups were not given it. Results: The results shows that the higher frequency of Entamoeba gingivalis in patients with Periodontitis 36.7%. Patients receiving chemotherapy showed higher frequency of E. gingivalis and Trichomonas tenax comparing with the control group 30% and 10%, 15% and 3.333% respectively. All rats which were deal with T. tenax still a life and with healthy gingiva, in the other hand, all rats in the 1st group that deal with E. gingivalis have been showed periodontal ulcers and two of them died after 10 days, while one rat of the 2nd group has been showed mild gingival inflammation with no death, and no ulceration, inflammation or death have been occurred in the control group. Conclusion: These findings suggest that: 1-Periodontal patients showed higher frequencies of E. gingivalis. 2-Patients receiving chemotherapy showed higher frequencies than the normal control. 3- In Vivo Entamoeba gingivalis may become pathogenic in individuals under chemotherapy.